Experimental investigation of the sand-stabilization potential of a plant-derived bio-mass - Bartley, Paul Andrew (Kansas State University, 2011)
The main objective of this study was to experimentally investigate the Mohr-Coulomb strength parameters of masonry sand mixed with varying amounts of water and lignin. Lignin is a plant-derived biomass, which is a co-product of bio-fuel production. It exhibits binding qualities when mixed with water thus making it an ideal candidate for sustainable non-traditional sand stabilization. An experimental program was devised and carried out to quantify the compaction and early age stress-strain and dilatancy responses of sand-lignin mixes. The program included sieve analysis, Atterberg limit tests, standard Proctor tests, and direct shear tests. The experimental results were used to find the cohesion and the angle of internal friction of the tested material, therefore determining the influence of the amount of lignin and water on the strength of the samples. An extensive data analysis was subsequently completed to gain deeper understanding of the underlying strength gain mechanism. It was found that the normalized cohesion benefit due to lignin is controlled by two variables; water to lignin ratio and void ratio. The lignin and water create a paste, which provides particle bonding at the contacts of sand particles, thus increasing the stress-bearing cross sectional area. Increase in the portion of cross-sectional area occupied by water and lignin normalized by gravimetric lignin content, increases the normalized cohesion up to a point, while the cohesion per gravimetric lignin content decreases with the increasing area ratio. This in turn indicates that cohesion increases only up to 6% of lignin, beyond which it starts to decrease due to the presence of too much fine material within the pores. The presence of lignin in the pores consistently decreases the angle of internal friction. However, for all configurations with lignin tested herein, cohesion was larger than for dry sand, thus indicating strength benefits at low confining pressures or at normal stresses below the so-called limiting normal stress.
Keywords: Sand; Lignin; Direct shear; Geotechnical engineering; Civil engineering; Civil Engineering (0543); Engineering (0537); Geotechnology (0428)